Composite lithium metal negative electrode and preparation method and application thereof
By coating high-entropy alloy coating on the lithium metal negative electrode and electrodepositing lithium metal, the problem of short dendritic growth and cycle life is solved, and efficient preparation of lithium metal negative electrode is achieved, which improves the efficiency and cycle life of Coulomb and simplifies the The preparation process was carried out.
Patent Information
- Application Number
- CN202411682487.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-07
AI Technical Summary
The existing lithium metal negative electrodes have short dendrite growth, volume expansion and cycle life, and the traditional high-entropy alloy preparation methods are complex and unsafe, resulting in low Coulomb efficiency.
The composite lithium metal negative electrode with a high-entropy alloy coating is coated with a copper foil surface, and high-entropy alloy particles are prepared by ball milling, and mixed with carbon material and adhesive in nitrogen methylpyrrolidone to form a slurry to form a coating on copper foil , lithium metal is loaded into a high entropy alloy coating by electrodeposition.
The uniform and controllable deposition of lithium metal is achieved, the nucleation overpotential is reduced, the alloying is prevented, the cycle life and first-time Coulomb efficiency are improved, and the preparation method is simple, safe, and easy to scale.
Smart Images

Figure CN119275241A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium metal batteries and specifically discloses a composite lithium metal negative electrode and a preparation method and application thereof. Background Art
[0002] Lithium metal batteries benefit from the high specific capacity (3860mAh / g) and the lowest electrode potential (-3.045V) of lithium metal negative electrodes, and are hailed as the most promising rechargeable battery technology. However, the growth of lithium metal negative electrode dendrites and the resulting large volume expansion, low Coulomb efficiency, and short cycle life limit its practical application. In order to solve these problems, researchers proposed to load lithium metal in a porous coating, and use the high specific surface area of the porous coating to reduce the current density during the lithium metal deposition process, so as to achieve uniform and reversible deposition of lithium metal. However, conventional porous coatings are difficult to form good wetting with lithium metal, so it is difficult to achieve uniform and reversible deposition. In this regard, some researchers proposed to modify the porous coating with active metals (such as zinc, tin, silver, etc.) that have good wetting effects on lithium to achieve uniform and reversible deposition of lithium metal and improve the cycle stability of the battery. However, active metals such as zinc, tin, and silver are easily alloyed with lithium, resulting in serious volume effects. For example, the process of alloying zinc, tin, and silver with lithium metal produces 98% (LiZn), 244% (Li 4.4 Sn) and 236% (Li 2.7 Ag) volume expansion. Active metal pulverization is prone to occur during repeated alloying and dealloying, which ultimately limits the improvement of the battery's cycle life. Therefore, it is necessary to develop a new wetting strategy to achieve reversible loading of lithium metal and then promote the application of lithium metal anodes.
[0003] Recently, researchers have proposed using high entropy alloys as lithium wetting sites. High entropy alloys are usually composed of five or more elements, and the wetting function of lithium metal is satisfied through an unlimited combination of elements, thereby achieving uniform and reversible lithium metal deposition. Invention patent CN 118287681 A prepares CuInNiSnCd high entropy alloy modified carbon fiber composites by methods such as precursor solution configuration, electrostatic spray gun spraying, and argon-hydrogen mixed gas high-temperature sintering reduction, and is used for reversible deposition and dissolution of metallic lithium, showing good cycle stability. However, this preparation method has a long and complicated process. In particular, the reduction of metal salts to metals requires the use of argon-hydrogen mixed gas, which has safety hazards. In addition, it must be pointed out that the high entropy alloy particles prepared by this method are nano-scale, with a very large specific surface area, and there are a large number of metals (indium, tin and cadmium) that are easily alloyed with lithium in the CuInNiSnCd high entropy alloy, resulting in serious interface side reactions in the early stage of the cycle and extremely low first coulomb efficiency (<40%). Similarly, invention patent CN 118389966 A prepares high entropy alloy @ carbon fiber composite nanomaterials by metal salt dissolution, electrostatic spinning and high temperature sintering reduction, which are used as negative electrode materials for lithium-ion batteries. Similarly, nanoscale high entropy alloy particles and a large amount of easily alloyed metals cause this material to also show a low first coulomb efficiency (~60%). Therefore, it is urgent to develop a simple and safe method for preparing high entropy alloys, while enabling high entropy alloy electrodes to achieve a high first coulomb efficiency and a long cycle life. Summary of the invention
[0004] In view of the common problems of composite lithium metal negative electrodes, the present invention aims to provide a composite lithium metal negative electrode and a preparation method and application thereof. The high entropy alloy particles in the present invention have good lithium wettability, can reduce the nucleation overpotential of lithium metal, effectively avoid volume effect and dendrite growth, and achieve long cycle life.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A composite lithium metal negative electrode is composed of a copper foil, a high entropy alloy coating composited on the surface of the copper foil, and lithium metal loaded in the high entropy alloy coating.
[0007] Furthermore, the high entropy alloy coating is obtained by coating a slurry prepared by mixing high entropy alloy particles, carbon material and adhesive. The thickness of the high entropy alloy coating is 50 to 400 μm, and the mass ratio of the high entropy alloy particles, carbon material and adhesive is (5 to 80):(5 to 80):(5 to 30).
[0008] Furthermore, the high entropy alloy particles are composed of five or more metals in equal molar ratios, wherein the metals include active metals and inert metals, wherein there is at least one and at most two active metals.
[0009] Furthermore, the active metal is selected from magnesium, aluminum, zinc, gallium, germanium, silver, cadmium, indium, tin, antimony, lead and bismuth; and the inert metal is selected from scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel and copper.
[0010] Furthermore, the carbon material is any one or more mixtures of conductive carbon, Ketjen black, graphite, graphene, carbon nanotubes, and carbon fibers.
[0011] Furthermore, the adhesive is a mixture of any one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyethylene oxide, polyacrylonitrile and polymethyl methacrylate.
[0012] The present invention also provides a method for preparing the composite lithium metal negative electrode, comprising the following steps:
[0013] (1) mixing five or more active metal or inert metal powders in equal molar ratios, and then placing them in a ball mill under argon atmosphere protection to prepare high entropy alloy particles by ball milling;
[0014] (2) uniformly dispersing the high entropy alloy particles, carbon material, and adhesive obtained in step (1) in nitrogen-methyl pyrrolidone to form a slurry, then coating the slurry on the surface of the copper foil, and drying the slurry to form a copper foil electrode modified with a high entropy alloy coating;
[0015] (3) The copper foil electrode modified with the high entropy alloy coating obtained in step (2) is used as the working electrode, and the lithium sheet is used as the counter electrode. Lithium metal is loaded into the high entropy alloy coating by electrodeposition in a 3.6M LiFSI / DME-TTE electrolyte to obtain a composite lithium metal negative electrode.
[0016] Furthermore, in the step (1), the material-to-ball ratio used in the ball milling is 1:10, the ball milling speed is 250-400 r / min, and the total ball milling time is 8-16 h, wherein the single ball milling time is 25 min and the intermittent time is 5 min.
[0017] Furthermore, the current density of the electrodeposition in step (3) is 0.5 to 8 mA / cm 2 The area capacity of electrodeposition is 1~6 mAh / cm 2 .
[0018] The present invention also provides the use of the composite lithium metal negative electrode in a lithium metal battery, wherein the composite lithium metal negative electrode is combined with a lithium iron phosphate positive electrode (LiFePO4) and a ternary nickel cobalt manganese positive electrode (LiNi x Co y Mn z O2, where x+y+z=1), lithium cobalt oxide positive electrode (LiCoO2), lithium manganese oxide positive electrode (LiMn2O4), and sulfur positive electrode constitute a lithium metal battery.
[0019] The composite lithium metal negative electrode of the present invention has the following advantages: the high entropy alloy particles present in the composite lithium metal negative electrode have good lithium wetting properties, which can effectively reduce the nucleation overpotential of lithium metal and achieve uniform and controllable lithium deposition. And the high entropy alloy particles are different from traditional lithium wetting metals, preventing complete alloying with lithium metal and causing particle pulverization. In addition, by adjusting the type of high entropy alloy elements and preparation parameters, the controllable preparation of high entropy alloys with high wettability and high stability can be achieved, and a long and stable cycle life can be achieved. Moreover, this preparation method is simple, safe, and easy to prepare and apply on a large scale.
[0020] Instruction Manual
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 This is the SEM image of the aluminum-titanium-iron-nickel-copper high entropy alloy particles in Example 1.
[0023] Figure 2 Schematic diagram of the structure of the composite lithium metal negative electrode in Example 1, wherein 1 is copper foil; 2 is a high entropy alloy coating; and 3 is a high entropy alloy particle.
[0024] Figure 3 1 and 2 are the deposition curves of the electrodes in Example 1, Comparative Example 1 and Comparative Example 2.
[0025] Figure 4 The cycle performance of the electrodes in Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0026] The following is a specific description of the preferred embodiments of the present invention, which does not constitute any limitation to the present invention. That is, the present invention is not meant to be limited to the above embodiments, and common modifications or alternative compounds in the technical field are all included in the scope defined by the claims of this application.
[0027] Example 1
[0028] Weigh 0.1 mol of aluminum powder, titanium powder, iron powder, nickel powder, and copper powder, and then put them into a ball mill protected by argon atmosphere with zirconium beads at a mass ratio of 1:10. At a ball milling speed of 300 r / min, ball milling for 12 h to obtain aluminum-titanium-iron-nickel-copper high entropy alloy particles ( Figure 1). Then, the aluminum-titanium-iron-nickel-copper high entropy alloy particles, conductive carbon, and polyvinylidene fluoride were uniformly mixed in a nitrogen-methylpyrrolidone solvent in a mass ratio of 20:60:20 to form a slurry, which was then coated on the surface of the copper foil and dried to form an aluminum-titanium-iron-nickel-copper high entropy alloy electrode with a coating thickness of 120 μm ( Figure 2 Then, the electrode was used as the working electrode, the lithium metal sheet was used as the counter electrode, and the organic lithium salt solution of 3.6 M LiFSI / DME-TTE was used as the electrolyte. 2 Current density and 1mAh / cm 2 Lithium deposition was performed under the same conditions and the charge-discharge cycle test was performed. The corresponding deposition curve is shown in Figure 3 , and the cycle performance is shown in Figure 4 . Thanks to the good lithium wetting properties of the Al-Ti-Fe-Ni-Cu high entropy alloy particles, the nucleation overpotential of the Al-Ti-Fe-Ni-Cu high entropy alloy electrode is only 157.3mV, and the first coulombic efficiency of this high entropy alloy electrode is as high as 91.8%, suggesting highly reversible lithium deposition and dissolution behavior. Moreover, this high entropy alloy electrode can achieve more than 320 stable cycles, and the coulombic efficiency is still maintained at 98%.
[0029] Comparative Example 1
[0030] Conductive carbon and polyvinylidene fluoride were uniformly mixed in a nitrogen methyl pyrrolidone solvent at a mass ratio of 8:2 to form a slurry, which was then coated on the surface of copper foil and dried to form a conductive carbon electrode with a coating thickness of 120 μm. This electrode was then used as the working electrode, the lithium metal sheet as the counter electrode, and a 3.6M LiFSI / DME-TTE organic lithium salt solution as the electrolyte at 5 mA / cm 2 Current density and 1mAh / cm 2 Lithium deposition was performed under the same conditions and the charge-discharge cycle test was performed. The corresponding deposition curve is shown in Figure 3 , and the cycle performance is shown in Figure 4 . The conductive carbon electrode has a large lithium nucleation overpotential (230.8 mV) because it has no lithium wetting sites. Moreover, the first coulombic efficiency of the conductive carbon electrode (90.6%) is also lower than that of the aluminum-titanium-iron-nickel-copper high-entropy alloy electrode. Therefore, this electrode can only achieve 157 stable cycles during long charge and discharge cycles, and then the coulombic efficiency fluctuates severely, which means severe lithium dendrite growth.
[0031] Comparative Example 2
[0032] Copper foil was used as the working electrode, lithium metal sheet was used as the counter electrode, and 3.6 M LiFSI / DME-TTE organic lithium salt solution was used as the electrolyte. 2 Current density and 1mAh / cm 2Lithium deposition was performed under the same conditions and the charge-discharge cycle test was performed. The corresponding deposition curve is shown in Figure 3 , and the cycle performance is shown in Figure 4 Compared with the Al-Ti-Fe-Ni-Cu high entropy alloy electrode and the conductive carbon electrode, the copper foil electrode has a large lithium nucleation overpotential (248.2 mV) and a low first coulombic efficiency (90.5%) due to the lack of lithium wetting sites and the planar structure. Moreover, the copper foil electrode can only achieve 73 stable cycles, and its life span is less than a quarter of that of the Al-Ti-Fe-Ni-Cu high entropy alloy electrode.
[0033] Example 2
[0034] The aluminum-titanium-iron-nickel-copper high entropy alloy particles prepared in Example 1, Ketjen black, and polyvinylidene fluoride were uniformly mixed in a nitrogen-methylpyrrolidone solvent in a mass ratio of 20:60:20 to form a slurry, and then coated on the surface of the copper foil using different scrapers, and dried to form aluminum-titanium-iron-nickel-copper high entropy alloy electrodes with thicknesses of 30, 50, 200, 400, and 600 μm, respectively. Then, this electrode was used as the working electrode, a lithium metal sheet was used as the counter electrode, and a 3.6M LiFSI / DME-TTE organic lithium salt solution was used as the electrolyte. The electrolyte was charged at 4 mA / cm 2 Current density and 1mAh / cm 2 Lithium deposition was performed at the same area capacity, and the charge-discharge cycle test was performed under the same conditions. The corresponding nucleation overpotential and cycle performance are shown in Table 1.
[0035] Table 1 Nucleation overpotential and cycling performance of high entropy alloy electrodes with different thicknesses
[0036]
[0037] The results show that the performance of the high entropy alloy electrode is optimal within the preferred coating thickness range (50-400 μm). When the coating thickness is too thin, the amount of high entropy alloy particles on the high entropy alloy electrode is too small, resulting in insufficient lithium wetting effect, making it difficult for lithium metal to be stably deposited, resulting in a larger nucleation overpotential and a lower first coulombic efficiency. Moreover, due to the thin coating, there are not enough cavities inside the coating to store lithium metal, resulting in lithium metal growth on the coating surface, which easily causes lithium dendrite growth, thereby reducing the cycle life of the electrode. When the coating thickness is too thick, the electrolyte wettability of the electrode deteriorates and the ion transmission distance increases, resulting in increased electrode polarization, thereby increasing the nucleation overpotential of the electrode. In addition, the coating of the thick electrode is prone to cracking and falling off, resulting in a low first coulombic efficiency and a short cycle life.
[0038] Example 3
[0039] Weigh 0.1 mol of titanium powder, manganese powder, iron powder, cobalt powder, and zinc powder, and then put them into a ball mill protected by argon atmosphere with zirconium beads in a mass ratio of 1:10. At a ball milling speed of 250r / min, ball milling for 14h to obtain titanium manganese iron cobalt zinc high entropy alloy particles. Then, titanium manganese iron cobalt zinc high entropy alloy particles, carbon fiber, and polytetrafluoroethylene are uniformly mixed in nitrogen methyl pyrrolidone solvent in a mass ratio of 5:75:20, 40:40:20, and 80:10:10 to form a slurry, which is then coated on the surface of copper foil and dried to form a titanium manganese iron cobalt zinc high entropy alloy electrode with a coating thickness of 100μm. Then use this electrode as the working electrode, a lithium metal sheet as the counter electrode, and a 3.6MLiFSI / DME-TTE organic lithium salt solution as the electrolyte at 3mA / cm 2 Current density and 1mAh / cm 2 Lithium deposition was carried out under the same conditions, and the charge and discharge cycle test was carried out. The corresponding cycle performance is shown in Table 2.
[0040] Example 4
[0041] The only difference from Example 3 is that the mass ratio of titanium-manganese-iron-cobalt-zinc high entropy alloy particles, carbon fibers, and polytetrafluoroethylene is 40:40:20, and the other implementations are the same as Example 3.
[0042] Example 5
[0043] The only difference from Example 3 is that the mass ratio of titanium-manganese-iron-cobalt-zinc high entropy alloy particles, carbon fibers, and polytetrafluoroethylene is 80:10:10, and the other implementations are the same as Example 3.
[0044] Comparative Examples 3 to 8
[0045] The titanium manganese iron cobalt zinc high entropy alloy particles, carbon fibers, and polytetrafluoroethylene prepared in Example 3 were uniformly mixed in a nitrogen methyl pyrrolidone solvent according to a mass ratio of 2:78:20, 85:5:10, 78:2:20, 5:85:10, 20:78:2, and 40:20:40 to form a slurry, which was then coated on the surface of a copper foil and dried to form a titanium manganese iron cobalt zinc high entropy alloy electrode with a coating thickness of 100 μm. This electrode was then used as a working electrode, a lithium metal sheet as a counter electrode, and a 3.6M LiFSI / DME-TTE organic lithium salt solution as an electrolyte at 3 mA / cm 2 Current density and 1mAh / cm 2 Lithium deposition was performed at the same area capacity, and the charge-discharge cycle test was performed under the same conditions. The corresponding nucleation overpotential and cycle performance are shown in Table 2.
[0046] Table 2 Nucleation overpotential and cycling performance of high entropy alloy electrodes prepared with different mass ratios of titanium-manganese-iron-cobalt-zinc high entropy alloy particles, carbon fiber, and polytetrafluoroethylene
[0047]
[0048]
[0049] The results show that within the preferred mass ratio of titanium-manganese-iron-cobalt-zinc high entropy alloy particles, carbon fibers, and polytetrafluoroethylene (5-80:5-80:5-30), the high entropy alloy electrode has the lowest nucleation overpotential, the highest first coulombic efficiency, and the best cycle life. When the content of high entropy alloy particles is insufficient, the electrode lacks sufficient lithium wetting sites, resulting in a large nucleation overpotential, reduced coulombic efficiency, and shortened cycle life. When the content of conductive carbon is insufficient, the conductivity of the electrode deteriorates, resulting in increased electrochemical polarization, increased nucleation overpotential, and reduced cycle life. When the content of adhesive is insufficient, it is easy to reduce the bonding force between the high entropy alloy coating and the copper foil, and reduce the bonding force between the particles inside the coating, which in turn leads to an increase in nucleation overpotential and a reduction in cycle life. When one of the high entropy alloy particles, conductive carbon, and adhesive is too large, it is easy to cause insufficient content of the other two, which in turn affects the electrode performance.
[0050] Example 6
[0051] (1) Preparation of titanium-iron-cobalt-nickel-copper high-entropy alloy particles (all made of inert metals): 0.1 mol of titanium powder, iron powder, cobalt powder, nickel powder, and copper powder were weighed, and then placed in a ball mill protected by argon atmosphere with zirconium beads at a mass ratio of 1:10. The ball mill was milled at a speed of 320 r / min for 15 h to obtain titanium-iron-cobalt-nickel-copper high-entropy alloy particles.
[0052] (2) Preparation of magnesium-iron-cobalt-nickel-copper high-entropy alloy particles (using an active metal): 0.1 mol of magnesium powder, iron powder, cobalt powder, nickel powder, and copper powder were weighed, and then placed in a ball mill protected by argon atmosphere with zirconium beads at a mass ratio of 1:10. The ball mill was milled at a speed of 320 r / min for 15 h to obtain magnesium-iron-cobalt-nickel-copper high-entropy alloy particles.
[0053] (3) Preparation of magnesium-aluminum-iron-cobalt-nickel high-entropy alloy particles (using two active metals): Weigh 0.1 mol each of magnesium powder, aluminum powder, iron powder, cobalt powder, and nickel powder, and then put them into a ball mill protected by argon atmosphere with zirconium beads in a mass ratio of 1:10. Ball mill at a speed of 320 r / min for 15 h to obtain magnesium-aluminum-iron-cobalt-nickel high-entropy alloy particles.
[0054] (4) Preparation of magnesium-aluminum-iron-cobalt-zinc high-entropy alloy particles (using three active metals): Weigh 0.1 mol of magnesium powder, aluminum powder, iron powder, cobalt powder, and zinc powder respectively, and then put them into a ball mill protected by argon atmosphere with zirconium beads in a mass ratio of 1:10. Ball mill at a speed of 320 r / min for 15 h to obtain magnesium-aluminum-iron-cobalt-zinc high-entropy alloy particles.
[0055] (5) Preparation of magnesium-aluminum-zinc-indium-tin high-entropy alloy particles (using five active metals): 0.1 mol of magnesium powder, aluminum powder, zinc powder, indium powder, and tin powder were weighed, and then placed in a ball mill protected by argon atmosphere with zirconium beads at a mass ratio of 1:10. The ball mill was milled at a speed of 320 r / min for 15 h to obtain magnesium-aluminum-zinc-indium-tin high-entropy alloy particles.
[0056] (6) Preparation and testing of high entropy alloy electrodes: The prepared high entropy alloy particles such as magnesium iron cobalt nickel copper, magnesium aluminum iron cobalt nickel, magnesium aluminum iron cobalt zinc, magnesium aluminum zinc indium tin, etc. were uniformly mixed with conductive carbon and polyacrylonitrile in a mass ratio of 15:70:15 in a nitrogen methyl pyrrolidone solvent to form a slurry, which was then coated on the surface of copper foil and dried to form a coating thickness of 150μm of titanium iron cobalt nickel copper, magnesium iron cobalt nickel copper, magnesium aluminum iron cobalt nickel, magnesium aluminum iron cobalt zinc, magnesium aluminum zinc indium tin, etc. High entropy alloy electrodes were then used as the working electrode, the lithium metal sheet was used as the counter electrode, and the organic lithium salt solution of 3.6M LiFSI / DME-TTE was used as the electrolyte. 2 Current density and 1mAh / cm 2 Lithium deposition was performed at the same area capacity, and the charge-discharge cycle test was performed under the same conditions. The corresponding nucleation overpotential and cycle performance are shown in Table 3.
[0057] Table 3 Nucleation overpotential and cycling performance of different high entropy alloy electrodes
[0058]
[0059] The results show that when there are one or two active metals in the high entropy alloy (MgFeCoNiCu high entropy alloy and MgAlFeCoNi high entropy alloy), the electrode exhibits high first coulombic efficiency and good cycling performance. When the high entropy alloy is composed entirely of inert metals, the electrode exhibits high nucleation overpotential and poor cycling performance, mainly due to poor lithium wetting properties and inability to stabilize the controllable deposition of lithium metal. When there are three to five active metals in the high entropy alloy, although the electrode exhibits a low nucleation overpotential, the alloying of lithium and active metals causes electrode pulverization, resulting in extremely poor cycling performance.
[0060] Example 7
[0061] Weigh 0.1 mol of titanium powder, iron powder, cobalt powder, nickel powder, and zinc powder, respectively, and then put them into a ball mill protected by argon atmosphere with zirconium beads in a mass ratio of 1:10. The ball milling speeds are 200, 250, 330, 400, and 500 r / min, respectively. Ball milling for 10 hours to obtain titanium iron cobalt nickel zinc high entropy alloy particles. Then, the prepared titanium iron cobalt nickel zinc high entropy alloy particles, Ketjen black, and polytetrafluoroethylene are uniformly mixed in a nitrogen methyl pyrrolidone solvent in a mass ratio of 10:70:20 to form a slurry, which is then coated on the surface of copper foil and dried to form different titanium iron cobalt nickel zinc high entropy alloy electrodes with a coating thickness of 140 μm. These electrodes are then used as working electrodes, lithium metal sheets as counter electrodes, and 3.6M LiFSI / DME-TTE organic lithium salt solution as electrolyte. At 2 mA / cm 2 Current density and 4mAh / cm 2 Lithium deposition was performed at the same area capacity, and the charge-discharge cycle test was performed under the same conditions. The corresponding nucleation overpotential and cycle performance are shown in Table 4.
[0062] Table 4 Nucleation overpotential and cycling performance of high entropy alloy electrodes prepared at different ball milling speeds
[0063]
[0064]
[0065] The results show that the performance of the high entropy alloy electrode is the best within the preferred ball milling speed range (250-400r / min). When the ball milling speed is too low, some metal powders fail to fully react to form high entropy alloys, which increases the nucleation overpotential of the electrode, reduces the first coulombic efficiency, and deteriorates the cycle performance. When the ball milling speed is too fast, the energy in the high entropy alloy synthesis process is too large, the temperature is too high, and the capacity causes the high entropy alloy particles to agglomerate together, which in turn affects the coulombic efficiency and cycle performance.
[0066] Example 8
[0067] Weigh 0.1 mol of titanium powder, iron powder, cobalt powder, nickel powder, zinc powder, and silver powder, and then put them into a ball mill protected by argon atmosphere with zirconium beads in a mass ratio of 1:10. At a ball milling speed of 330 r / min, ball mill for 5, 8, 12, 16, and 22 hours respectively to obtain titanium iron cobalt nickel zinc silver high entropy alloy particles. Then, the prepared titanium iron cobalt nickel zinc high entropy alloy particles, Ketjen black, and polytetrafluoroethylene are uniformly mixed in a nitrogen methyl pyrrolidone solvent in a mass ratio of 10:70:20 to form a slurry, which is then coated on the surface of copper foil and dried to form different titanium iron cobalt nickel zinc silver high entropy alloy electrodes with a coating thickness of 140 μm. Then, these electrodes are used as working electrodes, lithium metal sheets are used as counter electrodes, and 3.6M LiFSI / DME-TTE organic lithium salt solution is used as electrolyte. At 1 mA / cm2 Current density and 5mAh / cm 2 Lithium deposition was performed at the same area capacity, and the charge-discharge cycle test was performed under the same conditions. The corresponding nucleation overpotential and cycle performance are shown in Table 5.
[0068] Table 5 Nucleation overpotential and cycling performance of high entropy alloy electrodes prepared with different ball milling times
[0069]
[0070] The results show that the performance of the high entropy alloy electrode is the best within the preferred ball milling time range (8 to 16 hours). When the ball milling time is too short, the insufficient energy causes some metal powders to not fully react to form high entropy alloys, resulting in a large nucleation overpotential of the electrode, a decrease in the first coulombic efficiency, and poor cycle performance. When the ball milling time is too long, the energy in the high entropy alloy synthesis process is too large, the temperature is too high, and the capacity causes the high entropy alloy particles to agglomerate together, which also affects the performance of the high entropy alloy electrode.
[0071] Example 9
[0072] The titanium-iron-cobalt-nickel-zinc-silver high entropy alloy electrode prepared by ball milling for 12 h in Example 8 was used as the working electrode, the lithium metal sheet was used as the counter electrode, and the organic lithium salt solution of 3.6 M LiFSI / DME-TTE was used as the electrolyte. The electrolyte was charged at 0.2, 0.5, 2, 8, and 12 mA / cm 2 Current density and 3mAh / cm 2 Lithium deposition was performed at the same area capacity, and the charge-discharge cycle test was performed under the same conditions. The corresponding nucleation overpotential and cycle performance are shown in Table 6.
[0073] Table 6 Nucleation overpotential and cycling performance of high entropy alloy electrodes at different current densities
[0074]
[0075] The results show that as the current density gradually increases, the nucleation overpotential of the high entropy alloy electrode gradually increases. This is because at a smaller current density, the number of electrons per unit time is small, and they can fully combine with the lithium ions in the electrolyte to form lithium metal. When the current density is too large, the number of electrons per unit time is large, the lithium ions near the electrode are quickly consumed, and the lithium ions in the solution cannot be quickly replenished, resulting in increased electrochemical polarization and increased nucleation overpotential. However, in the preferred current density range (0.5-8 mA / cm 2), the first coulombic efficiency and cycle life of the high entropy alloy electrode are the longest. When the current density is too small, the nucleated lithium metal is in contact with the electrolyte for a long time, which leads to the time of aggravating the interfacial side reaction; and the particles of lithium metal nucleation are larger under low current density, which easily leads to the growth of lithium metal outside the high entropy alloy coating, thus reducing the coulombic efficiency and cycle life of the electrode. When the current density is too large, the electrode is prone to the growth of lithium dendrites, and serious interfacial side reactions occur, which also reduce the coulombic efficiency and cycle life of the electrode.
[0076] Example 10
[0077] The titanium-iron-cobalt-nickel-zinc-silver high entropy alloy electrode prepared by ball milling for 12 h in Example 8 was used as the working electrode, the lithium metal sheet was used as the counter electrode, and the organic lithium salt solution of 3.6 M LiFSI / DME-TTE was used as the electrolyte. 2 At current densities of 0.5, 1, 2.5, 6, and 10 mAh / cm 2 Lithium deposition was performed at the same area capacity, and the charge-discharge cycle test was performed under the same conditions. The corresponding nucleation overpotential and cycle performance are shown in Table 7.
[0078] Table 7 Nucleation overpotential and cycling performance of high entropy alloy electrodes at different current densities
[0079]
[0080]
[0081] The results show that in the optimal area capacity range (1-6 mAh / cm 2 ), the high entropy alloy electrode has the highest first coulombic efficiency and the longest cycle life, while the nucleation overpotential of the electrode is independent of the area capacity. When the area capacity is too small, the lithium metal deposited in the high entropy alloy coating is relatively loose and easily reacts with the electrolyte, causing a decrease in coulombic efficiency and cycle life. When the area capacity is too large, there is not enough cavity inside the high entropy alloy coating to store lithium metal, which then causes lithium metal to grow on the surface of the high entropy alloy coating, which in turn causes lithium dendrite growth, triggering serious interface side reactions, reducing coulombic efficiency and shortening cycle life.
[0082] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A composite lithium metal negative electrode, characterized in that: The composite lithium metal negative electrode is composed of a copper foil, a high entropy alloy coating composited on the surface of the copper foil, and lithium metal loaded in the high entropy alloy coating.
2. The composite lithium metal negative electrode according to claim 1, characterized in that: The high entropy alloy coating is obtained by coating a slurry prepared by mixing high entropy alloy particles, carbon material and adhesive. The thickness of the high entropy alloy coating is 50~400 μm, and the mass ratio of the high entropy alloy particles, carbon material and adhesive is (5~80):(5~80):(5~30).
3. The composite lithium metal negative electrode according to claim 2, characterized in that: The high entropy alloy particles are composed of five or more metals in equal molar ratios, wherein the metals include active metals and inert metals, wherein there is at least one and at most two active metals.
4. The composite lithium metal negative electrode according to claim 2, characterized in that: The active metal is selected from magnesium, aluminum, zinc, gallium, germanium, silver, cadmium, indium, tin, antimony, lead and bismuth; the inert metal is selected from scandium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel and copper.
5. The composite lithium metal negative electrode according to claim 2, characterized in that: The carbon material is any one or more of conductive carbon, Ketjen black, graphite, graphene, carbon nanotubes and carbon fibers.
6. The composite lithium metal negative electrode according to claim 2, characterized in that: The adhesive is a mixture of any one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyethylene oxide, polyacrylonitrile and polymethyl methacrylate.
7. A method for preparing a composite lithium metal negative electrode according to any one of claims 1 to 6, characterized in that The following steps are involved: (1) Active metal or inert metal powders are mixed in equal molar ratios according to five or more compositions, and then placed in a ball milling jar under argon atmosphere protection to prepare high entropy alloy particles by ball milling; (2) uniformly dispersing the high entropy alloy particles, carbon material, and adhesive obtained in step (1) in nitrogen-methylpyrrolidone to form a slurry, then coating the slurry on the surface of a copper foil, and drying the slurry to form a copper foil electrode modified with a high entropy alloy coating; (3) The copper foil electrode modified with the high entropy alloy coating obtained in step (2) is used as the working electrode, and the lithium sheet is used as the counter electrode. Lithium metal is loaded on the high entropy alloy coating by electrodeposition in a 3.6 M LiFSI / DME-TTE electrolyte to obtain a composite lithium metal negative electrode.
8. The method for preparing a composite lithium metal negative electrode according to claim 7, characterized in that: In the step (1), the material-to-ball ratio used in the ball milling is 1:10, the ball milling speed is 250-400 r / min, and the total ball milling time is 8-16 h, wherein the single ball milling time is 25 min and the intermittent time is 5 min.
9. The method for preparing a composite lithium metal negative electrode according to claim 7, characterized in that: The current density of the electrodeposition in step (3) is 0.5-8 mA / cm 2 The area capacity of electrodeposition is 1~6 mAh / cm 2 .
10. Use of the composite lithium metal negative electrode according to any one of claims 1 to 6 in a lithium metal battery, characterized in that: A lithium metal battery is formed by combining a composite lithium metal negative electrode with a lithium iron phosphate positive electrode, a ternary nickel cobalt manganese positive electrode, a lithium cobalt oxide positive electrode, a lithium manganese oxide positive electrode, and a sulfur positive electrode.
Citation Information
Patent Citations
CuInNiSnCd high-entropy alloy / carbon fiber composite material and preparation method and application thereof
CN118287681A